Development and investigation of LC light shutters for a welding automatic mask - Kolomzarov, Yu.; Oleksenko, P.; Sorokin, V.; Tytarenko, P.; Zelinskyy, R. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2004)
Elements of technology to produce liquid crystal (LC) light shutters for a welding automatic mask with the built-in transparent heater for operating LC layer were developed. Experimental samples of light shutters were created using the developed technology, and their parameters and characteristics were investigated. Measuring the “switch-on” times of the created light shutters has shown that the transition from the transparent state to the opaque one within the temperature range from –20 up to +50 °C lasts less than 1.5 ms. This value meets the requirements of international standards.